2017
DOI: 10.18325/jkmr.2017.27.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Report on 3 Cases of Lateral Epicondylitis Treated with Musculotendinous Releasing Manual Therapy after Acupuncture Treatment

Abstract: We researched 3 patients diagnosed as Lateral epicondylitis (Tennis elbow). We considered it as tendinosis including irregular collagen fiber's pattern. So, acupuncture therapy and musculotendinous releasing manual therapy were used to treat the patients. We measured their pain and functional disorder by visual analogue scale (VAS), Patient-Rated Tennis Elbow Evaluation (PRTEE), and a dynamometer before and after treatment. As a result, VAS and PRTEE significantly reduced and grasping power was also improved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…1). There were 9 RCTs [16][17][18][19][20][21][22][23][24] and 18 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] case reports included in the review. The main characteristics of these studies was presented in tables (Tables 2 and 3).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…1). There were 9 RCTs [16][17][18][19][20][21][22][23][24] and 18 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] case reports included in the review. The main characteristics of these studies was presented in tables (Tables 2 and 3).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
“…The highest frequency of treatment sessions in case reports was 57 [38], and the lowest was 1 session [35,42]. The number of treatment sessions were varied amongst the 18 case reports [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42].…”
Section: Analysis Of Treatment Sessionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Korean medicine, various treatments such as herbal medicines [8], acupuncture [9], fire acupuncture [10], electroacupuncture stimulation [11] and Chuna therapy [12] are selected as conservative treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacopuncuture has the effect of controlling the meridians of the acupuncture treatment, and the treatment of conditions/ diseases through the pharmacological reaction of the medicines [13]. Kim et al [14] reported a case of bee venom treatment, Park et al [15] reported 2 cases of scolopendra pharmacopuncture as a treatment, Choi et al [16] reported a case of anti-inflammatory pharmacopuncture as a treatment, and Uhm et al [17] reported 4 cases of combined pharmaconpuncture treatment for lateral epicondylitis.…”
Section: Introductionmentioning
confidence: 99%